El despido con responsabilidad patronal: nueva visión, a partir de la entrada en vigor de la reforma procesal laboral (R.P.L) - Ureña Chaves, José Andrés (2026)
This article analyzes the concept of free dismissal after three years of the implementation of this new labor regulation. For this, the jurisprudential criteria issued by the Court are taken as a basis. From this analysis, it is concluded that there are some limiting conditions on free dismissal, so that once the worker proves that there are signs of discrimination, the employer must demonstrate that dismissal was based on objective causes.